Unidirectional focusing for broadband Lamb guided wave based on mode conversion - Haifei Zhu; Xuan Zhang; Wenjie Liu; Houyou Long; Ying Cheng; Xiaojun Liu (Communications Physics)
Abstract Metamaterials promise to revolutionize elastic devices, with applications spanning wireless communication, structural health monitoring and microfluidic technology. Nevertheless, unidirectionally manipulating broadband elastic waves remains challenging due to their inherent complexity of polarization. Here, we introduce a method to control the transmission of broadband Lamb waves unidirectionally by utilizing mode conversion and selection. The elastic meta-atoms showcased  >30 dB contrast in transmissions between forward and backward illumination scenarios within 251-345.9 kHz. Leveraging the disparity in phase velocities between S 0- and A 0-mode Lamb waves, the meta-atom enables broadband phase modulation. We realize a unidirectional focusing lens that exhibits a concentration of out-of-plane displacements for S 0-mode Lamb waves under forward excitation, while reflecting those excited backward. An enhanced unidirectionally-transmitted meta-atom displaying  <3 dB forward transmission within 293.3-333.6 kHz is further developed by incorporating an A 0-mode reflector. Our proposal advances the manipulation of broadband plate waves, holding significant potential for multifunctional on-chip elastic devices.